An exploration of printing challenges and strategies among Malaysia commercial printers / Noor Azly Mohammed Ali - Mohammed Ali, Noor Azly (2018)
The printing market across the globe today is very challenging with many printing companies are striving to sustain their existence in the market. Malaysia printers are not excluded and received the similar pressure. Realizing the affect of this scenario in the long run, this study explored the printing challenges faced by the Malaysia commercial printers and the strategies used to maintain in the market from the management's perspectives. A qualitative with the exploratory research design was used. The data collection was done in two stages. First, a preliminary study was conducted with fifteen companies in order to have a general understanding about the scenario and challenges faced by Malaysia printers. The themes from this stage were then analysed and then collapsed into four main themes: market challenge, technology development, human resources challenges, and quality implementation and enforcement. The themes generated from the first stage were then used to further explore the scenario at four large commercial printing companies that are established. In depth interviews were conducted with twenty-two to investigate whether the companies encountered the challenges and to compare the strategies used to retain in the market. All the participated printing companies highlighted and agreed that the global printing challenges impacted their printing businesses. It is recommended that printing companies to smartly utilize their existing resources, keep abreast with the latest technology, aware and adapt to market changes, and improve employees' competency. Practically, this study could help Malaysia commercial printing companies to improve their businesses performances and stay competitive. Additionally, the sustainability strategies identified can be shared and benchmarked by other printers in improving their performance. The findings also could help relevant agencies to review current policies to augment the overall performance of Malaysia printing industries. Theoretically, the findings of this study enrich the existing literature with the current issues or challenges faced and strategies adopted by the Malaysia printers, which is very minimal being empirically studied before. This study focused on large printers, thus, future studies are encouraged to explore on Small and Medium Enterprise (SME) printers who play vital role in Malaysia printing industry.